2016
DOI: 10.1111/jcmm.12924
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous COL4A4 missense mutation in a Chinese family with focal segmental glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is the most common glomerular histological lesion associated with high‐grade proteinuria and end‐stage renal disease. Histologically, FSGS is characterized by focal segmental sclerosis with foot process effacement. The aim of this study was to identify the disease‐causing mutation in a four‐generation Chinese family with FSGS. A novel missense mutation, c.1856G>A (p.Gly619Asp), in the collagen type IV alpha‐4 gene (COL4A4) was identified in six patients and it co‐segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
(52 reference statements)
3
24
0
Order By: Relevance
“…Analyzing correlations between genotype and phenotype, we found that the clinical phenotypes of the 3 probands manifested in mild phenotypes of microhematuria, proteinuria without higher serum creatinine levels, and progressive renal injury. Published data showed that most of the heterozygous mutations found in COL4A4 are glycine at different positions [Kamiyoshi et al, 2016;Wu et al, 2016]. Compared to other reports, except for the clinical phenotype caused by heterozygous COL4A4 , the glycine substitution reported here is similar to that found in the literature [Jefferson et al, 1997;Kamiyoshi et al, 2016;Wu et al, 2016].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Analyzing correlations between genotype and phenotype, we found that the clinical phenotypes of the 3 probands manifested in mild phenotypes of microhematuria, proteinuria without higher serum creatinine levels, and progressive renal injury. Published data showed that most of the heterozygous mutations found in COL4A4 are glycine at different positions [Kamiyoshi et al, 2016;Wu et al, 2016]. Compared to other reports, except for the clinical phenotype caused by heterozygous COL4A4 , the glycine substitution reported here is similar to that found in the literature [Jefferson et al, 1997;Kamiyoshi et al, 2016;Wu et al, 2016].…”
Section: Discussionsupporting
confidence: 74%
“…Published data showed that most of the heterozygous mutations found in COL4A4 are glycine at different positions [Kamiyoshi et al, 2016;Wu et al, 2016]. Compared to other reports, except for the clinical phenotype caused by heterozygous COL4A4 , the glycine substitution reported here is similar to that found in the literature [Jefferson et al, 1997;Kamiyoshi et al, 2016;Wu et al, 2016]. We also reported 2 nonsense heterozygous mutations in 2 probands, manifesting in mild phenotypes.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations